Analisis Faktor-faktor Yang Mempengaruhi Keputusan Berkunjung Pada Wisata Buana Alit Bengkulu Tengah - Sri Wahyuni; Ida Anggriani; Iswidana Utama Putra (UNIVED Press, 2022)
The purpose of this study is to find out the factors that influence the decision to visit Buana Alit Tourism, Central Bengkulu. The analytical method used is multiple linear regression, coefficient of determination (R2) and hypothesis testing (t-test and F-test) with the help of SPSS program (statistical package for social science) version 22. The sample of this study amounted to 75 respondents. The results of multiple linear regression obtained Y = 25.304 + 0.117X1 + 0.061X2+ 0.124X3 + 0.056X4 + 0.197X5 + 2.729. The results of the multiple linear regression with a regression constant value is 25.304, it means that if the location, facilities, image, price, service are 0 (zero), then the decision to visit Buana Alit Tourism Central Bengkulu the value is 25.304. From the coefficient of determination, the R value is 0.730 and R Square (R2) is 0.533 or (53.3%). This showed that there is a very strong relationship between location, facilities, image, price, service, and the decision to visit because the value of r count is greater than the value of r table (0.2273). The results of the t-test on the location variable (X1) obtained a significance value of less than 0.05 (0.029 < 0.05), it can be concluded that location has a significant effect on the decision to visit Buana Alit Tourism, Central Bengkulu. The results of the t-test on the Facility variable (X2) obtained a significance value of less than 0.05 (0.049 < 0.05), it can be concluded that the facility has a significant effect on the decision to visit Buana Alit Tourism, Central Bengkulu. The results of the t test on the Image variable (X3) obtained a significance value of less than 0.05 (0.002 < 0.05), it can be concluded that the image has a significant effect on the decision to visit Buana Alit Tourism, Central Bengkulu. The results of the t-test on the price variable (X4) obtained a significance value of less than 0.05 (0.023 <0.05), it can be concluded that the price has a significant effect on the decision to visit Buana Alit Tourism, Central Bengkulu. The results of the t-test on the Service variable (X5) obtained a significance value of less than 0.05 (0.000 <0.05), it can be concluded that service has a significant effect on the decision to visit Buana Alit Tourism, Central Bengkulu. Based on the F test, the significance value is less than 0.005 (0.000 < 0.05), it can be concluded that simultaneously (location, facilities, image, price, service) there is a significant influence on the decision to visit Buana Alit Tourism, Central Bengkulu.